2008
DOI: 10.1590/s0100-879x2008005000048
|View full text |Cite
|
Sign up to set email alerts
|

Association between dental-oral health in young adults and salivary glutathione, lipid peroxidation and sialic acid levels and carbonic anhydrase activity

Abstract: The aim of the present study was to evaluate the relationship between salivary oxidative stress and dental-oral health. Healthy young adults, matched for gender and age, with (N = 21, 10 men, mean age: 20.3 ± 1 years) and without (N = 16, 8 men, mean age: 21.2 ± 1.8 years) caries were included in this study. The World Health Organization (WHO) caries diagnostic criteria were used for determining the decayed, missing, filled teeth (DMFT) index. The oral hygiene and gingival status were assessed using the simpli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 17 publications
(19 reference statements)
3
28
0
1
Order By: Relevance
“…[19,[21][22][23] On the other hand, some of our results were not in agreement with other authors. [23][24][25] This conflict may be due to the difference in method of analysis as our study were able to determine the concentration of salivary CA VI while Frasseto et al [25] used the zymography method to quantitatively determine the activity of salivary CA VI. [24] Their results indicate significantly higher activity of CA in stimulated than non-stimulated saliva in both examined groups, while Surdilović et al [20] reported a positive correlation between CA VI concentration and saliva secretion.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…[19,[21][22][23] On the other hand, some of our results were not in agreement with other authors. [23][24][25] This conflict may be due to the difference in method of analysis as our study were able to determine the concentration of salivary CA VI while Frasseto et al [25] used the zymography method to quantitatively determine the activity of salivary CA VI. [24] Their results indicate significantly higher activity of CA in stimulated than non-stimulated saliva in both examined groups, while Surdilović et al [20] reported a positive correlation between CA VI concentration and saliva secretion.…”
Section: Resultsmentioning
confidence: 77%
“…[23][24][25] This conflict may be due to the difference in method of analysis as our study were able to determine the concentration of salivary CA VI while Frasseto et al [25] used the zymography method to quantitatively determine the activity of salivary CA VI. [24] Their results indicate significantly higher activity of CA in stimulated than non-stimulated saliva in both examined groups, while Surdilović et al [20] reported a positive correlation between CA VI concentration and saliva secretion. [26] It should be realized that several factor affect the saliva composition that could changes according to the flow rate, nature and duration of stimulation, and the time of day at which samples are collected.…”
Section: Resultsmentioning
confidence: 77%
“…The study by Oztürk et al [2008] found no significant difference in CAVI concentration when caries and caries-free young adults were compared. On the other hand, the investigation performed by Kivelä et al [1999] has shown that a low CAVI concentration is associated with a higher caries index; it has also shown a negative correlation between CAVI concentration and DMFT index in individuals with poor oral hygiene.…”
mentioning
confidence: 89%
“…Glutathione directly scavenges free radicals, sometimes act as a substrate for glutathione peroxidases and glutathione Stransferases during the detoxification of ROS [7,8]. Recently studies have been carried out on salivary glutathione levels in patients with diabetes, dental caries and head and neck squamous cell carcinoma [3,9,10]. The aim of our study was to evaluate the levels of salivary glutathione in oral leukoplakia and oral squamous cell carcinoma patients.…”
Section: Introductionmentioning
confidence: 99%